200 Hemoglobin A1c does not Predict Severity of Erectile Dysfunction. Issue 1 (1st April 2022) - Myers, A.; Haehn, D.; Ball, C.; Shumate, A.; Broderick, G.
ABSTRACT: Introduction: Erectile dysfunction (ED) is a common consequence of Diabetes Mellitus (DM). The medical literature is inconclusive as to which DM related morbidities improve with better glycemic control. Surgical literature often associates infection outcomes with DM and with glycemic control. There is limited research on the relationship between Hemoglobin A1c and severity of vascular ED. Objective: To evaluate the relationship between hemoglobin A1c (HbA1c) and severity of vascular ED in men with DM diagnosed with vascular ED by penile color duplex Doppler ultrasound (CDDU). Methods: We retrospectively analyzed patients with a history of DM who underwent intracavernous injection followed by CDDU at our institution between 2005 and 2019. CDDU findings including peak systolic velocities (PSV), primary diagnosis after CDDU, and resistive indices (RIs) were recorded. Doppler diagnosis was based on post stimulation PSV and RI. Arterial Insufficiency (AI) was classified as PSV < 25 cm/s (severe), or (moderate) PSV 25-34.9 cm/s with RI ≥ 0.90. Corporal veno-occlusive disease (CVOD) was classified as PSV ≥ 35 cm/s with RI < 0.90. Mixed ED was classified as PSV 25-34.9 cm/s with RI < 0.90. HbA1c was recorded at time of assessment. Among our cohort of 1490 men who had CDDU, 520 had DM: 130 with CDDU diagnosis of ED, 270 with CDDU diagnosis of ED + Peyronie's disease (PD), 94 with PD alone and 26 with normal vascular erections on CDDU and no PD. The 130 patients with DM diagnosed with ED without presence of PD were included in our analysis. We used a Kruskal-Wallis rank sum test to evaluate the overall association between HgA1c and CDDU diagnosis (AI, CVOD, and mixed ED). Spearman rank correlation tests were used to explore the relationship of HbA1C with PSV and RI. Results: Among the 130 men with DM + ED without PD, the median age was 61 y (range 20-79 y), 76 (58%) had hypertension, 37 (28%) had heart disease, median BMI was 30.7 kg/m2 (range 21.2-48.9 kg/m2), and median HgbA1C was 7.0 (range 5.0-11.0). PDE-5 inhibitor use was reported in 119/129 (92.2%) and among those who reported using it 108/119 (90.8%) reported PDE-5 inhibitor failure. CDDU diagnoses were 53 (40.8%) AI, 44 (33.8%) CVOD, and 33 (25.4%) mixed vascular (25%). The median (interquartile range) HbA1c was 7.0 (6.1-7.8) in men with AI, 7.1 (6.3-8.0) in men with CVOD, and 6.7 (6.1-7.0) in men with mixed ED. We did not find evidence of a relationship between HbA1c and severity of vascular ED (Kruskal-Wallis test P = 0.25). We also did not find evidence of a correlation of HbA1c with either post-stimulation PSV (Spearman rank correlation = 0.04, P=0.68) or RI (Spearman rank correlation = -0.03, P = 0.79). Conclusions: Median HbA1c did not vary with the vascular diagnosis of men with DM + ED (AI vs. CVOD vs. Mixed Vascular). DM is a significant risk factor for ED and HbA1c is used to monitor and advise patients. We found no predictive relationship between HbA1c and type of vascular ED as defined by CDDU. Disclosure: No